Potential of medicinal plants for internal diseases in the dayak jangkang community, sanggau regency, west kalimantan, indonesia - Benediktus Ege; Hendrikus Julung; Markus Iyus Supiandi; Susriyati Mahanal; Siti Zubaidah (JPBIO (Jurnal Pendidikan Biologi), 2021)
Dayak Jangkang people’s knowledge about the potential use of plants as medicine to cure internal diseases has not been found in the scientific literature. This research aims to record the types of plants (local name, scientific name, family), plant organs used, processing methods, specifications of plant benefits used by Dayak Jangkang people to treat internal diseases. The research approach used is qualitative descriptive. The data collection tool used is a semi-structured interview sheet. The informant who helped the research process was as many as ten people. Informant was determined using purposive sampling techniques. The data is analyzed descriptively based on interviews and literature studies. The results of the study were obtained as many as 34 types of plants that were used by the Dayak Jangkang tribe to treat internal diseases. The number of families used as many as 19, with the most families being Zingiberaceae.